1994
DOI: 10.1891/0886-6708.9.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Child Sexual Abuse and Adult Revictimization With Women of Color

Abstract: Clinical researchers examining the long-term consequences of child molestation have reported that female survivors of child sexual abuse experience a higher risk of sexual assault as adults. However, very little literature has focused on the child and/or adult sexual victimization of women from different ethnic or cultural backgrounds. In examining the long-term consequences of child sexual abuse, this investigation examined the rates of sexual revictimization of women of color. A multiethnic (white, African-A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
75
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 0 publications
11
75
1
2
Order By: Relevance
“…African American, White, and Latina women reporting CSA were significantly more likely to report adult rape; however, this relation was not found for Asian American women (Urquiza & Goodlin-Jones, 1994). Merrill et al (1999) also found that CSA predicted rape for African American, white, and Latina women; however, CPA predicted rape only for African American women.…”
Section: Women At Risk For Less Social Powermentioning
confidence: 84%
See 2 more Smart Citations
“…African American, White, and Latina women reporting CSA were significantly more likely to report adult rape; however, this relation was not found for Asian American women (Urquiza & Goodlin-Jones, 1994). Merrill et al (1999) also found that CSA predicted rape for African American, white, and Latina women; however, CPA predicted rape only for African American women.…”
Section: Women At Risk For Less Social Powermentioning
confidence: 84%
“…A review of individual studies suggest that between 16% and 72% of women who experience CSA are revictimized (Messman & Long, 1996). Urquiza & Goodlin-Jones (1994) found that rates of revictimization varied for different ethnic groups, such that 61.5% of African American who reported CSA also reported rape, while 44.2% of Whites and 40% of Latinas who reported CSA also reported rape. Merrill et al (1999), however, did not find differing rates of revictimization for African American, White, and Latina women.…”
Section: Revictimization: a Common And Severe Outcome Of Child Abusementioning
confidence: 99%
See 1 more Smart Citation
“…In community population samples, it is black women who are most at risk of sexual aggression (Abbey et al, 1996;Urquiza & Goodlin-Jones, 1994); however, in college and university samples, white women are found to be most at risk (Kalof, 2000;Koss et al, 1987;Mills & Granoff, 1992). And still yet, Bohn (2003) provides data that suggest Native American women are most at risk.…”
Section: Victimsmentioning
confidence: 99%
“…Some studies have found that African American women report significantly higher rates of CSA compared with White, Hispanic, or Asian-American women (Scott, Lefley, & Hicks, 1993;Urquiza & Goodlin-Jones, 1994), and that White women report CSA at significantly higher rates than Hispanic or Asian-American women (Urquiza & Goodlin-Jones, 1994).…”
mentioning
confidence: 99%